PORTRAIT OF POST COVID-19 HISTORY LEARNING IN CLASS XA OF SUNAN GUNUNGJATI VOCATIONAL SCHOOL BLIMBINGSARI - Ladayna Hulus Utami; Mahfud; I Kadek Yudiana (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Education is basically inseparable from the educational problems that have occurred so far. These problems can hinder the expected learning process in education. The educational problems that are currently being experienced are currently experiencing a transitional period caused by the covi-19 virus epidemic. This then has an impact on changes in the educational order that has been structured so far. This study aims to describe the portrait of post-covid-19 history learning in class XA at ​​SMK Sunan Gunungjati, post-covid learning is carried out face-to-face in a limited way by adjusting the curriculum. This study uses a descriptive qualitative research method. The techniques used in this study were interviews, observation, and document studies. Data analysis in this study includes data collection, data reduction, data presentation, and drawing conclusions. Checking the validity of the data using triangulation of data, theory, methods, and sources. The purposes of this research are: 1) to find out the learning process in post-covid 2) to describe the obstacles to the post-covid-19 learning process.